The effect of using virtual reality headset during imagery on netball players' imagery ability, mood, physiological parameter and shooting performance - Rosli, Siti Nur Syafiqah (2018)
Imagery one of psychological training skill (PST) that use both mind and body where it involves the process of create or re-creating an experience in the mind by using all the human senses. Meanwhile, recently, many sport scientists have developed a new system that uses technology in order to improve athletes’ performance. One of the technology uses is the virtual reality (VR) headset. However, there is only limited research can be found in combining VR with imagery, thus, this study was carried out to investigate the effect of using virtual reality headset during imagery on netball players’ imagery ability, mood, physiological parameters and netball shooting performance. 9 netball players from SMK Putera, Kelantan, completed the study. Their age ranged between 13 to 15 years old (mean±SD = 13.44±.882). They were grouped into two research conditions: control group namely no VR group (NVR) and intervention group namely VR group (VR) using a cross-over study design. The same participants participated in both research conditions with two-week resting in between. They underwent 10 sessions of imagery training. To measure imagery ability, Sport Imagery Ability Measurement (SIAM) was employed. Brunel Mood Scale (BRUMS) was used to measure the mood states of the participants, including anger, confusion, depression, fatigue, tension and vigour. Physiological parameters measured are oxygen saturation (SpO2) and heart rate (HR) where pulse oximetry was employed. To measure the shooting performance of the participants, pre-test and post-test of netball shooting was carried out. The result showed that both groups have a similar imagery ability measure by SIAM. A similar result also observed in BRUMS where imagery using VR headset seemed does not influence participants’ mood. Repeated measure ANOVA for shooting performance showed an increase in shooting score occurred in both groups. As a conclusion, there were improvements in the shooting performance of the netball players in both groups.